The Narrative Turn in Career Development Theories: An Integrative Perspective - Rossier, Jérôme (2020)
During the past 70 years, diverse vocational theories have focused on various important topics such as career choice processes or person–organization fit and adaptation to describe people’s career development. More recently, narrative approaches have been proposed by several authors inspired by dialogical self theory or the life story model of identity in career counselling interventions. This narrative turn encourages career interventions to focus more on the meaning experiences; the reflexive processes involved; and the contextual aspects of career paths, such as the life design paradigm. Narrative identity facilitates understanding these dynamics once it is conceived as a meta-capacity, allowing people to self-direct and design their actions within these continuous interrelations. Narrative identity is built on a dialogical relationship, allowing individuals to situate themselves in social space and strengthen subjectivity, reflexivity, and intentionality. Considering the narrative processes for intervention research will permit examination in greater detail of the processes underlying change. This chapter thus discusses how narrative career development theories, such as the career construction theory or the life-long self- construction theory, can complement existing approaches and constitute an integrative and articulated framework if they take account of previously acquired knowledge.